Kajian Yuridis Warisan Tanpa Kejelasan Ahli Waris: (Studi Putusan No. 200/Pdt.P/2023/PN Jkt.Tim) - Ruminingsih Ruminingsih; Vivin Astharyna Harysart; Mohamad Fikri (Pusat Riset dan Inovasi Nasional, 2025)
An heir whose whereabouts are unknown refers to a person presumed missing, with no confirmation of life or death. This thesis examines the juridical settlement of inherited assets under civil law, focusing on Case Study Decision Number: 200/Pdt.P/2023/PN Jkt.Tim. The research employs a normative legal method, analyzing statutory regulations (law in book). According to Article 463 of the Civil Code, an heir whose whereabouts cannot be confirmed still retains inheritance rights, supported further by Article 467. However, if the court officially declares the missing person as deceased, their legal status as an heir ceases, and their position is transferred to a substitute heir. This substitution is governed by Article 841 of the Civil Code, which assigns all rights and obligations of the original heir to the replacement. Importantly, the substitute heir may only assume control of the inherited assets after a court decision has declared the original heir legally missing or deceased. Without such a ruling, no transfer or control of inheritance can occur. This ensures legal certainty and protects the rights of all parties involved in the inheritance process.